Resources versus Capabilities in Social Justice - Yilmaz, Ensar (SAGE PUBLICATIONS INDIA PVT LTD, 2016)
Over the last decades, economists, political theorists and philosophers have debated the question of what the proper metric of justice is. In other words, they have sought to answer the questions what should we look at, when evaluating whether one state of affairs is more or less just than another? Should we evaluate the distribution of happiness? Or wealth? Or some combination of these and other factors? The resourcist approach and the capability approach as egalitarian theories of social justice are two prominent answers to these questions. While the former approach has been developed by the studies of John Rawls and Donald Dworkin, the latter approach has been associated with the studies of Amartya Sen and Martha Nussbaum. A fundamental debate between these approaches continues over what should be distributed. This article attempts to bridge the gap between these approaches. By this we aim to bring their different perspectives together to reconsider the relationship between resource and the capability approach, and to open up a new insight to understand both approaches as complementary theories, rather than purely rival theories of justice.
Keywords: Resources; capabilities; social justice; redistribution; EQUALITY; Business & Economics